Pengembangan Media Puzzle pada Materi Iman kepada Allah Kelas II Madrasah Ibtidaiyah Pondok Pesantren Teknologi Darussalam Salu Induk - Kanna Rombe Allo, Sul Aisyah; Fakhrunnisaa, Nur; Thaha, Hisban (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
In order to gain insight into the development process, verification test outcomes, and practicality of using puzzle media in Islamic religious education, this study examines its impact on class II students' learning about faith in the Book of Allah at Madrasah Ibtidaya Pondok Pesantren Technologi Darussalam Salu Utama. Research Methodology The Dick and Carey Development Model used in R&D. Pondok Pesantren